2020
DOI: 10.1016/j.childyouth.2020.105355
|View full text |Cite
|
Sign up to set email alerts
|

Impact of “e-Learning crack-up” perception on psychological distress among college students during COVID-19 pandemic: A mediating role of “fear of academic year loss”

Abstract: Highlights “e-Learning crack-up” perception has a significant impact on student’s psychological distress. Fear of academic year loss is the key responsible factor for psychological distress during COVID-19. Prediction relevance of psychological distress pointed out a good fit with R 2 = 0.996 and Q 2 = 0.656.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
377
1
17

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 473 publications
(473 citation statements)
references
References 53 publications
23
377
1
17
Order By: Relevance
“…Most students reported that they found it difficult to stay motivated and on task. Losing motivation during the pandemic is a well-documented phenomenon (Hasan & Bao, 2020;Purwanto, et al, 2020).…”
Section: Overall Findings Discussion and Implicationsmentioning
confidence: 99%
“…Most students reported that they found it difficult to stay motivated and on task. Losing motivation during the pandemic is a well-documented phenomenon (Hasan & Bao, 2020;Purwanto, et al, 2020).…”
Section: Overall Findings Discussion and Implicationsmentioning
confidence: 99%
“…The most emphasized thing on the characteristics of online learning is towards student independence and control is with students [20], for that effort related to it is important to do. However, common problems experienced in online learning today are limited infrastructure [1], [2], limited human resource capabilities [20], and low motivation [5], [6], [7], [8].…”
Section: A E-learning During Covid-19 Pandemicmentioning
confidence: 99%
“…The second problem is the decline in students' mental health during the lockdown period which has an impact on the low motivation of students towards the online learning system during Covid-19 pandemic. [5], [6], [7], [8]. However, this pandemic condition cannot be avoided, therefore efforts to increase user acceptance and motivation of online learning are also important [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that even after MOOCs, their theoretical benefits to the e-learning experience did not meet the expectations, as there exist high dropout rates [2]. As today's incident does not tolerate dropping out, learners are at even greater risk to continue a course without any interest or attention [3]. Other factors affecting e-learning across web eras were reviewed for all intended stakeholders, providing a comprehensive view on e-learning advances.…”
Section: Introductionmentioning
confidence: 99%
“…As MOOC is a platform where learners are self-driven to enrol [27], the online educational experience should be attractive for each learner to ensure persistency, especially when there is no other option during this current global pandemic [3]. Many studies have proposed different approaches that ought to influence the learner's completeness in e-learning systems as presented in the following sub-sections.…”
Section: Introductionmentioning
confidence: 99%